A social learning theory model for understanding team-based professional communication learning for computer science students - Kalil, C. A.; Grant, T. (South African Journal of Higher Education, 2021)
The study interrogates an annual course with undergraduate computer science students that takes place against the background of national student protests at universities across South Africa to effect equitable access to universities. It uses reflections by computer science students of their experience of collaborative work on a Scenario Pedagogy (SP) course, as well as the results of a survey of student collaborative practices in a digital space as a window into their learning trajectories. The study demonstrates and offers an understanding of how SP can contribute to developing computer science students as communicators in their discipline at university and future workplaces. It explores the usefulness of Communities of Practice (COP) and Knowledgeability across Landscapes of Practice (KLP) theory as an analytical tool-set as well as a descriptive language for investigating and explaining learning events. The changing and changed landscape of higher education and the world of work present new challenges and opportunities, particularly in curriculum development and delivery. Utilising “authentic” pedagogies and social learning theory provides appropriate tools for meeting these challenges. Exploring reflective practices and their contribution to the emerging of transformed practices and identities in the South African higher education sector would be a fruitful avenue of future research.